Pelatihan Soft Skills untuk Meningkatkan Daya Saing Angkatan Kerja Muda di Desa Situ Gadung Kabupaten Tangerang - Hermawati, Rahmi; Handayani, Rima; Kustini, Endang (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The increasing competitiveness of the job market requires young workers to possess not only technical abilities but also strong soft skills. In response to this need, a Community Service Program (PKM) titled Soft Skills Training to Improve the Competitiveness of Young Workers in Situ Gadung Village, Tangerang Regency was conducted. This program aimed to equip the youth in Situ Gadung Village with essential soft skills to enhance their employability and adaptability in the workforce. The activity was carried out on April 26–27, 2025, in Situ Gadung Village, involving 14 lecturers from Universitas Pamulang as facilitators and 24 local participants. The training used a combination of methods including material presentation, hands-on practice, group discussion, and question-and-answer sessions to ensure effective learning. The topics covered communication skills, teamwork, time management, problem-solving, and work ethics. The results showed increased awareness and understanding among participants regarding the importance of soft skills, with positive feedback indicating that the training was beneficial and applicable to real-life work settings. This PKM activity contributes to community development by fostering a more prepared and competitive young workforce.